PENERAPAN AUDIT INTERNAL PADA SISTEM PENGENDALIAN INTERNAL PERUSAHAAN DALAM MENINGKATKAN EFEKTIFITAS KINERJA PEJUALAN PERUSAHAAN PADA PERIODE TAHUN 2021- 2023 - Fauji, Achmad; Z.A, Ghonimah (STIE PENA, 2025)
The research activity focuses on the problem of whether the internal control system has an effect on sales effectiveness with internal audit as an intervening variable. The analysis tool used is multiple regression, using a Likert scale and questionnaire. The sample method with random sampling. Data analysis uses a research methodology with a classical assumption test, t test, f test, and determination test. Primary data was obtained from several employees totaling 55 people in the company. Several research results were obtained, including that the internal control system and internal audit both have an effect on sales effectiveness. The internal control system has an indirect effect through internal audit as an intervening variable. The level of measurement that the direct influence is greater than the indirect influence, which indicates that the internal control system has a more significant direct influence on sales effectiveness. Keywords: Internal Control System, Internal Audit, Sales Effectiveness